Macroeconomic Determinants of Public Health Expenditure in India: Evidence from an ARDL Approach - Sinha, Jitendra Kumar (Journal of Behavioral Economics and Policy, 2025)
Public health expenditure in India remains persistently low relative to expanding healthcare needs driven by demographic growth, epidemiological transition, and macroeconomic volatility. Identifying the structural determinants of public health spending is therefore essential for designing fiscally sustainable and equitable health financing strategies. This study examines the long-run and short-run drivers of public health expenditure in India using annual national-level time-series data for the period 2000–2024. An Autoregressive Distributed Lag (ARDL) modelling framework with an error correction mechanism (ECM) is employed, given its suitability for small-sample analysis and its capacity to accommodate variables integrated of mixed orders. Augmented Dickey–Fuller tests confirm stationarity at first difference, supporting the application of the ARDL bounds testing approach to assess cointegration and dynamic adjustments. The empirical findings reveal a stable long-run equilibrium relationship between public health expenditure and its macroeconomic, fiscal, demographic, and labour market determinants. Per capita income and tax revenue exhibit positive and statistically significant long-run effects, indicating that economic expansion and improved revenue mobilisation enhance fiscal space for health investment. Infant mortality and unemployment significantly influence expenditure, underscoring the roles of health vulnerability and labour market stress. Inflation exerts a positive cost-push effect, reflecting rising input costs. The error correction term is negative and highly significant, confirming rapid convergence toward equilibrium. Short-run dynamics indicate lagged fiscal responses but immediate expenditure adjustments to adverse health conditions. The results suggest that while public health spending in India is income-responsive, institutional and structural constraints limit its adequacy, necessitating reforms that link growth to protected and efficient health financing.